2005
DOI: 10.1158/1055-9965.epi-04-0236
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Instability in Peripheral Blood Lymphocytes and Risk of Prostate Cancer

Abstract: Prostate cancer is an extremely complex disease, and it is likely that chromosomal instability is involved in the genetic mechanism of tumorigenesis. Several chromosomes have been labeled as “players” in the development of prostate cancer, among them chromosome 1 and X chromosome have been reported to harbor prostate cancer susceptibility loci. However, there is little information regarding the background levels of chromosome instability in these patients. In this pilot study, we examined spontaneous chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
(58 reference statements)
2
7
0
Order By: Relevance
“…Their spontaneous rates were significantly increased in ten patients, as well. These results are similar to data published by El-Zein et al (2005), who also examined spontaneous chromosome instability in prostate cancer patients and healthy controls. They used short-term lymphocyte cultures and evaluated chromosomal instability using fluorescence in situ hybridization assay with two probes targeting specific regions on chromosome X and chromosome 1.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Their spontaneous rates were significantly increased in ten patients, as well. These results are similar to data published by El-Zein et al (2005), who also examined spontaneous chromosome instability in prostate cancer patients and healthy controls. They used short-term lymphocyte cultures and evaluated chromosomal instability using fluorescence in situ hybridization assay with two probes targeting specific regions on chromosome X and chromosome 1.…”
Section: Discussionsupporting
confidence: 92%
“…Although there are numerous reports in literature on prostate cancer, there is little information regarding the spontaneous background levels of chromosomal alterations in these patients (De Ruyck et al 2008; Dotan et al 2004; El-Zein et al 2005; Ozen et al 2000; Steiner et al 2002; Varga et al 2005; Verhagen et al 2002; Wolter et al 2002). Varga et al reported that spontaneous, as well as radiation-induced, micronuclei were not increased in sporadic prostate cancer patients compared to healthy male controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies found that the X-chromosome had a significantly higher mean level of spontaneous breaks in patients compared to those observed in controls. These results showed that spontaneous CIN in PBLs might be a potential biomarker for PC susceptibility [ 59 ]. In fact, an increased frequency of CIN in PBLs reflects the early biological effects of genotoxic carcinogens and individual cancer susceptibilities [ 60 ].…”
Section: Cin and Cancermentioning
confidence: 99%
“…Cancer Genet Cytogenet 137(1): 59-63 [ 105 ] El-Zein R et al (2005). Cancer Epidemiol Biomarkers Prev 14: 748-52 [ 30 ] Kolusayin Ozar MO et al (2005). J Exp Clin Cancer Res 24: 217-22 [ 34 ] Petersen I et al (2009).…”
Section: Introductionmentioning
confidence: 99%